Employee Perspectives on the Transition of Normal Work Return after Flexible Working Period - Darina, Mawar Kusuma (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to provide an alternative narrative about the employees' perceptions and experiences regarding the transition to a normal working mode after experiencing a period of flexible work on a return-to-work (RTW) policy. This research uses a qualitative method with an interpretivism approach. Utilizing semi-structured in-depth interviews with 17 participants that were selected by using purposive sampling from various professions and companies. The findings of this research reveal difficulties encountered during the implementation of work changes among employees. These difficulties are evident through observed patterns of thinking and resistance stemming from the loss of opportunities to engage in flexible work arrangements. The implications of this study hold relevance for governmental bodies and organizations as they seek to establish congruence between their objectives and the interests of employees. By considering the insights gained from this research, decision-makers can foster an environment that harmonizes the needs of both entities, contributing to enhanced organizational outcomes and employee satisfaction. Emphasizing employee narratives as change executioners during work transition, this study further looks at attributes workers displayed during three distinct change period phases. This study contributes to the subject of organizational management by extending prior research on the return-to-work process across various contexts and situations.